2021
DOI: 10.1017/s1368980021000173
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prenatal artificial sweeteners consumption on birth outcomes: a systematic review and meta-analysis

Abstract: Objective: To examine the influence of prenatal artificial sweetener consumption on birth outcomes. Design: Systematic review and meta-analysis. Setting: Online databases (MEDLINE, CINAHL, EMBASE, Cochrane Library, Scopus, Web of Science, FSTA - the food resource database, and ClinicalTrials.gov) were searched up to April 9, 2020. Studies of all designs (except case studies and reviews) were eligible, which contained information on the relevant population (pregnant wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 57 publications
0
9
0
1
Order By: Relevance
“…However, no systematic review on human studies of NNS for weight gain in offspring was available. Cai et al [ 30 ] conducted a meta-analysis to assess the relationship between NNS intake during pregnancy and birth weight by including three cohort studies [ 6 , 15 , 31 ]. Nevertheless, several methodological defects existed in their review.…”
Section: Discussionmentioning
confidence: 99%
“…However, no systematic review on human studies of NNS for weight gain in offspring was available. Cai et al [ 30 ] conducted a meta-analysis to assess the relationship between NNS intake during pregnancy and birth weight by including three cohort studies [ 6 , 15 , 31 ]. Nevertheless, several methodological defects existed in their review.…”
Section: Discussionmentioning
confidence: 99%
“…Cai et al conducted a meta-analysis finding that women who consumed sucralose and other NNS during pregnancy delivered babies with an increased birth weight and a decreased gestational age compared to women reporting not to utilize NNS [ 12 ]. Moreover, the ingestion of aspartame or sucralose during gestation increased body mass index (BMI) and fat mass of children at three years, while also producing elevated body weight and adiposity in C57BL/6 mice [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Work by Laforst-Lapointe et al showed that maternal consumption of AS during pregnancy was associated with infant gut microbiota and metabolic modifications concomitant with an increased infant body mass index [11]. A recent systematic review demonstrated that maternal exposure to AS during pregnancy is associated with an increased risk of preterm birth and increased birth weight [13]. Previous work by our group has demonstrated that exposure to Ace-K and FR results in maternal glucose intolerance and reduced pregnancy duration, as well as glucose intolerance and adipocyte hypertrophy in female but not male offspring [14][15][16].…”
Section: Introductionmentioning
confidence: 99%